Peningkatan Kualitas Bacaan Alquran Melalui Metode Talaqqi pada Murid TPQ Desa Landbaw - Randy Rahma Putra; Umi Fauziah; Ulil Albab; Annisa ‘Ainurrahmatin Najiyah; Nanda Alhusna (Lembaga Pengembangan Kinerja Dosen, 2024)
Landbaw Village is situated in Tanggamus Regency's Gisting District. This village created a Quranic Education Park to instill moral principles and Quranic education in children from a young age. A crucial venue for children's character development and formation is the Quranic Education Park (TPQ). From an early age, children are provided with the chance to study and explore the sacred book of the Quran, adhere to Islamic principles, and develop admirable qualities through this establishment. They are given a brief introduction to the Quran, helped to comprehend its lessons, and urged to live their lives in accordance with Islamic principles. The Landbaw village now offers the option to learn using the talaqqi method. With this method, there is direct communication between the between the teacher and the children.